Antihyperglycemic and antioxidant activities of twig extract from Cinnamomum osmophloeum - Lin, Gong-Min (J Tradit Complement Med, 2015)
This is the first report concerning the α-glucosidase, α-amylase and protein tyrosine phosphatase 1B (PTP1B) inhibitory activities of cinnamon twig extracts. Comparing the antihyperglycemic activity of renewable plant parts, indigenous cinnamon (Cinnamomum osmophloeum; 土肉桂 tǔ ròu guì) twig extracts (CoTE) showed better α-glucosidase and α-amylase activities than leaf, 2-cm branch and 5-cm branch extracts. Chemotype of C. osmophloeum has no influence on the antihyperglycemic activities and proanthocyanidin contents of CoTE. Among four soluble fractions obtained from CoTE by following bioactivity-guided fractionation procedure, the n-butanol soluble fraction (BSF) with abundant proanthocyanidins and condensed tannins, exhibited the best antihyperglycemic and PTP1B inhibitory activities. In addition, the BSF displayed the excellent DPPH free-radical scavenging and ferrous ion-chelating activities. The antihyperglycemic and antioxidant activities of all four soluble fractions from CoTE showed high correlation coefficient with their proanthocyanidin and condensed tannin contents. Furthermore, CoTE had no toxicity on 3T3-L1 preadiocytes. Results obtained demonstrated that CoTE has excellent antihyperglycemic, antioxidant and PTP1B inhibitory activities, and thus has great potential as a source for natural health products.